2003
DOI: 10.1103/physreve.68.041702
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of helix unwinding in ferroelectric liquid crystals

Abstract: In bulk ferroelectric liquid crystals, the molecular director twists in a helix. In narrow cells, this helix can be unwound by an applied electric field or by boundary effects. To describe helix unwinding as a function of both electric field and boundary effects, we develop a mesoscale simulation model based on a continuum free energy discretized on a two-dimensional lattice. In these simulations, we determine both the director profile across the cell and the net electrostatic polarization. By varying the cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In order to obtain a suitably tractable model for simulations, many approaches have been developed for understanding helix unwinding, which take several simplifications. [7,8] For example, the contribution of the dielectric interaction energy density is suggested by Uto [9] to be neglected in the description of the unwinding process generated by an electric field. However, the dielectric contribution into the free energy density is proportional to the squared electric field.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a suitably tractable model for simulations, many approaches have been developed for understanding helix unwinding, which take several simplifications. [7,8] For example, the contribution of the dielectric interaction energy density is suggested by Uto [9] to be neglected in the description of the unwinding process generated by an electric field. However, the dielectric contribution into the free energy density is proportional to the squared electric field.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed Bayth et al [34] which are reported that when the helical pitch of the smectic C* was confined between two parallel glass with a homogeneous planar anchoring causes an unwound of the helical structure which is proportional to the cell thickness. This transition is due to the result of the competition between the energy cost of the lines of dechiralisation slightly dependent on the thickness and that to the unwound of helix which is highly depends to the cell thickness.…”
Section: Polymer Network Morphology By Afm Investigationsmentioning
confidence: 99%
“…In 1977, Meyer [2] gave a model for the field-induced helical unwinding process in SmC * , analogous to that in cholesteric liquid crystals also proposed by him [3]. The continuity of directors along the normal to layers is not broken during the unwinding process because the unwinding occurs through the pitch diverging, that is, the pitch increases with an increase in the applied field and finally it diverges to infinity at the critical field for completely unwound state E c [4][5][6][7][8]. This is called the diverging pitch model and is based on the continuum approximation, where the elastic energy is proportional to the square of the deformation of directors, hence the deformation by an (a) E-mail: jvij@tcd.ie external force should be spatially continuous for minimizing the elastic energy.…”
mentioning
confidence: 99%